A Cross-Sectional Study on the Impact of COVID-19 on Patient Confidence Regarding Dental Visits of Residents of Angeles, Pampanga Ages 18-59/Micah Mae M. Mandanas, Sandy S. Villanueva and Katrina Christine Q. Yu. - Mandanas, Micah Mae M.
INTRODUCTION: The pandemic has brought significant changes to healthcare delivery, especially in dentistry, due to the risk of virus transmission from aerosol- generating procedures. The study aims to determine the impact of COVID-19 pandemic on patients’ confidence regarding dental visits. It also aims to determine the mode for each factor that has affected patient confidence in dental visits, the proportion of patients who had visits to the dentist before and during the COVID-19 pandemic, and the prevalence ratio of patients who had visits to the dentist before and during the COVID-19 pandemic.